2013
DOI: 10.1177/0009922813488645
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Serious Bacterial Infections in Febrile Children With Sickle Cell Disease

Abstract: We had an incidence of 16.0% for serious bacterial infections in febrile children with sickle cell disease, with the majority of patients diagnosed with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
26
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 20 publications
9
26
5
Order By: Relevance
“…Our finding suggests that bacteremia is more common in children with SCD in Nigeria than in developed countries. It is tempting to assume that the lower incidence of bacteremia in London and United States may be due to routine penicillin prophylaxis and vaccinations in those settings 15,16. However, the majority of the etiological agents of bacteremia in the present study were Gram negative organisms especially Klebsiella pneumoniae which corroborates two previous studies in Nigeria 3,17.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding suggests that bacteremia is more common in children with SCD in Nigeria than in developed countries. It is tempting to assume that the lower incidence of bacteremia in London and United States may be due to routine penicillin prophylaxis and vaccinations in those settings 15,16. However, the majority of the etiological agents of bacteremia in the present study were Gram negative organisms especially Klebsiella pneumoniae which corroborates two previous studies in Nigeria 3,17.…”
Section: Discussionsupporting
confidence: 88%
“…The 13.8% incidence observed in this study is higher than 3.4% reported in a retrospective study in London and 1.1% in another retrospective study in the United States of America 15,16. It is however lower than 32.5% reported in Benin City, Nigeria, about two decades earlier 3.…”
Section: Discussioncontrasting
confidence: 76%
“…In this study, most of the children had been diagnosed by newborn screening (87.3%), which entails a very high percentage of patients with complete vaccination status (94.4%) and receiving penicillin prophylaxis (96.3%) since the first months of life. All these factors probably explain the low rate of CSBI (4.1%) and bacteremia (1.9%) in this cohort, similarly to that in other studies performed in developed countries . We did not find any episodes of confirmed pneumococcal infection, unlike some recent studies that reported cases of invasive pneumococcal disease by serotypes not included in pneumococcal conjugated vaccines .…”
Section: Discussionsupporting
confidence: 82%
“…However, the HGUGM is a reference center of the Madrid area for patients with SCD, so this cohort represents a broad sample of these children for a low‐prevalence country such as Spain and it may be quite representative of the pediatric population with SCD in developed countries. Another limitation of this study was the inclusion of all episodes of ACS in the possible SBI group, similarly to what has been done in other studies, because of the difficulty of excluding bacterial pneumonia or a viral‐bacterial coinfection in cases of ACS. However, to solve this possible bias, we analyzed separately the low‐risk factors for CSBI and ACS.…”
Section: Discussionmentioning
confidence: 99%
“…The leading organism for bacteremia remained S. pneumoniae despite implementing vaccination and penicillin prophylaxis policies 16 (Supporting Information Table S2). [8][9][10]12,[19][20][21][22][23][24][25][26][27] These data further demonstrate that bacteremia will be identified within 48 h for the overwhelming majority of febrile SCA patients. One patient in our cohort identified with bacteremia after 48 h grew Bordetella holmesii, a rare Gram-negative bacterium that has been identified as a slow growing bacteria in patients with asplenia.…”
Section: Discussionmentioning
confidence: 92%